2008
DOI: 10.2196/jmir.1065
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Internet-Based Hearing Test—Comparison with Established Methods for Detection of Hearing Loss

Abstract: Background Hearing impairment is most accurately measured by a clinical pure-tone audiogram. This method is not suitable for large-scale, population-based epidemiological studies as it requires that study participants visit a clinic with trained personnel. An alternative approach to measuring hearing ability is self-estimation through questionnaires, but the correlation to clinical audiometric tests varies.Objective To evaluate an Internet-based hearing test pilot compared to a question about self-estimated he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 19 publications
(19 reference statements)
1
33
0
1
Order By: Relevance
“…Although online data collection may not solve traditional problems faced for reaching the population sample [22], several studies argue in favor of high acceptability and feasibility of web-based questionnaires [23][24][25]. Moreover, the latter, particularly usable for analytical studies that focus on associations between variables [26], have major advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Although online data collection may not solve traditional problems faced for reaching the population sample [22], several studies argue in favor of high acceptability and feasibility of web-based questionnaires [23][24][25]. Moreover, the latter, particularly usable for analytical studies that focus on associations between variables [26], have major advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Internet-based hearing tests have been proposed as a means of hearing testing although there are serious practical concerns such as calibration accuracy and lack of control on environmental noise levels (Bexelius et al, 2008). This application although controversial, may well serve a purpose of increasing public awareness and as a preliminary 14 screening for hearing loss.…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…Three reports described self-test screening procedures; two of these used speech-in-noise screening and one described pure tone audiometric screening. [16][17][18] Smits and colleagues 16 reported on the development and validation of a speechin-noise screening procedure using triple digits and an adaptive procedure that can be used reliably over the telephone and computer headsets. They subsequently reported on a national self-screening program in the Netherlands using this test to screen large numbers of adolescents and adults using the telephone (n ¼ 6,351) or Internet (n ¼ 30,260).…”
Section: Audiological Screeningmentioning
confidence: 99%
“…A self-test, Internet-based, pure tone audiometry screening procedure was reported by Bexelius and colleagues. 18 This proof-ofconcept study screened patients by determining threshold frequencies between 500 and 8,000 Hz as against a more conventional screening criterion that assesses hearing at a preset intensity across a limited range of frequencies. This study tested the members of a hunting organization and reported poor participation in the self-test, but demonstrated that Internet-based hearing screening tests can be performed.…”
Section: Audiological Screeningmentioning
confidence: 99%